A constituição dos sentidos na educação infantil - Roquini, Elizabeth Aparecida Alves (2019)
This research work entitled "The constitution of senses in early childhood education", with a qualitative character, shows the didactics developed in the educational process initially triggered in an adapted thematic room, called "TENDA DOS SENTIDOS", and then, in bibliographical form . The children attending this space "Tenda dos Sentidos" were 0 to 5 years old, and the institution chosen to conduct the research was a Municipal School of the South of Minas Gerais. Realizing that play is part of the process of teaching learning in children's education, play has become an object and, in this sense, our thesis is that its didactics seeks to apply principles with the purpose of developing in children the cognitive skills to make them critical reflective Knowing that teaching work is an integral part of the educational process, the research problem is faced with the questioning: Pedagogical practices in the field of Early Childhood Education produce the construction of learning through play and experiences involving the senses, care and affections In order to answer this and other questions that emerge in the development of the research, the investigative tools anchored in the cultural studies that cover the references of Rubem Alves and Antônio Torres and Jorge Larrosa were constructed.